Analysis of Physics Concepts in Crop Drying Technology - Perdana, Dimas Halim; Fajari, Alfian; Sudarti, Sudarti; Mahmudi, Kendid (International Journal of Education, Information Technology, and Others, 2025)
The drying process of crops is a crucial stage in production that affects quality and efficiency. One of the principles of physics that plays an important role in this process is the concept of heat, which allows the transfer of heat from heat sources to crops to evaporate their moisture content. This study aims to analyze the physics concepts in the process of drying crops using Rotary Dryer and Bed Dryer technology. The research is conducted through literature studies using relevant scientific articles and sources. The results show that both technologies involve the mechanism of heat transfer by conduction and convection, as well as the interaction of centrifugal and centripetal forces in the drying process. The conclusion of this study confirms that understanding the concept of physics allows the optimization of energy use, thereby improving the efficiency of the drying process and the quality of crop yields. This finding is expected to be a reference in Physics learning, especially in understanding the application of physics concepts in the crop processing industry.